INFLUENCE OF FINANCIAL LITERACY, FINANCIAL SOCIALIZATION, AND CONSUMPTIVE TRAITS ON FINANCIAL MANAGEMENT BEHAVIOR OF PAYLATER USERS (LOCUS OF CONTROL AS MODERATOR) - Setya, Ifnu; Jati, Pradana; Eko, Dwi; Nur, Amalia (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
The development of financial technology (fintech) has revolutionized how individuals manage their finances, with paylater services emerging as one of the most popular innovations in Indonesia. While offering payment flexibility, uncontrolled use may lead to financial problems. This study aims to analyze the influence of financial literacy, financial socialization, and consumptive behavior on the financial management behavior of paylater users, with locus of control as a moderating variable. A quantitative approach was employed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) involving 378 respondents in Central Java. The results indicate that financial literacy, financial socialization, and consumptive behavior have a positive and significant effect on financial management behavior. However, locus of control does not consistently act as a moderator that strengthens the relationships among variables; in some cases, it even weakens the effect. These findings highlight the importance of financial education strategies that not only enhance financial literacy but also take individual psychological factors into account. This study contributes academically and provides policy recommendations to improve financial literacy and promote wiser financial behavior in the digital era.